"Be Fierce, Believe in Yourself, and Find Your People": A Roundtable Discussion about Disability and Performance. Issue 2 (May 2018) - Lipkin, Joan; Haddad, Ryan
Abstract : This is an intergenerational discussion between Joan Lipkin, artistic director and co-founder of The DisAbility Project, and Ryan Haddad, an actor, playwright, and autobiographical performer based in New York City. Lipkin and Haddad discuss how they came to their work in disability arts and culture, how they develop the work, and their aesthetic and political approaches to that work. They offer thoughts on the importance of disability theater in the present age, and offer advice to disabled artists who seek to develop their own work. The conversation was conducted over a series of weeks and has been edited.